KLASIFIKASI KUALITAS MUTU TELUR AYAM RAS BERDASARKAN FITUR WARNA DAN TEKSTUR - Miftahus Sholihin; M Ghofar Rohman (Universitas Islam Lamongan, 2018)
Egg quality is determined by the quality of the inside and outside of the egg. To find out the quality of eggs canbe by looking at the outside in the form of skin condition, shape, size, and egg weight. In this study a system isdesigned to function to determine the quality of egg quality based on color and texture features. Broadlyspeaking, the system built consists of 4 main processes. This process begins with pre-processing which aims toimprove image quality and also to change the image size. The next process is segmentation to get the egg object.The next process is feature extraction which aims to get the characteristics of each egg object. The last processis a classification that aims to determine the class of egg images entered by the user, the method used is knearest neighbor. The data used in this study were 147 egg images consisting of 85 eggs of data testing and 62eggs of training data. The highest accuracy obtained from this study is 82.3% with a value of 8